El compromiso político: Razones para actuar independientemente del deseo - Lucena Cid, Isabel Victoria (Nómadas. Critical Journal of Social and Juridical Science, 2011)
This article analyzes Searle’s thesis according to which all political power represents a deontic power related to rights, duties, obligations, authorizations, permissions, authority, etc. This conception leads to understand to us the power and the constituent functions of status irremediably tie to the collective acceptance and constitutive rules. Notions like linguistic constitution of deontic powers, the reasons to act independently of desire, the normative rationality and the collective acceptance of the political systems, constitute some of angular stones of a conceptual frame whose social, institutional and politic realistic vision have important implications in the scope of the legal, political and moral philosophy.